Length and weight relationship bronze featherback (Notopterus notopterus, Pallas 1769) in Sei Pulai Reservoir, Bintan Regency, Riau Island - Susiana Susiana; Dedy Kurniawan; Ulfa Rianti; Rapita Rapita; Daza Septian Nugraha; Edo Edo; Kamal Rudin; Bim Aprilyanto; Hardi Wiradinata; Pangga Kurnia Dialam; Rochmady Rochmady (Sangia Research Media and Publishing LLC, 2021)
Sei Pulai Reservoir is one of the sources of raw water for the people of Bintan Island, Riau Islands, to be precise in Tanjungpinang and its surroundings. Sei Pulai Reservoir is also a habitat for belida fish (Notopterus notopterus). The purpose of this study was to determine the relationship between length and weight of belida fish (N. notopterus) in Sei Pulai Reservoir, Bintan Regency. Sampling was carried out once a week from April to May 2021 based on fishermen's catch areas and fish habitats. The relationship between length and weight of male fish is W = 0,00000006L3,4839 which indicates a positive allometric growth pattern and for female fish is W = 0,000002L2,761which indicates a negative allometric growth pattern.